Effect of the Weight Training Period on the Increase in the 100 Meter Run in Indonesian NPC Athletes - Nurhidayat Nurhidayat; Akhmad Azlan Khoirurrozikin; Eko Sudarmanto; Bima Febriyanto; Haris Nugroho (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
The population and samples in this study were all 10 sprint athletes in the  Indonesian National Paralympic Committee (NPC)  10 men.  The sampling technique uses purposive samples, as it takes into account the characteristics of the sexes.  The quasi-experimental method with a quantitative approach, as for the design of this study using pretest-posttest one group design. Data analysis techniques use descriptive statistics and inferential statistics. Descriptive analysis aims to describe the characteristics of this study while inferential analysis uses paired one sample test (t_test) at a significant level of α = 0.05, and overall data analysis uses the SPSS program version 26.0. The results of this study can be concluded that the period of laden training can increase the running speed of 100 meters of Indonesian NPC athletes. However, it is necessary to conduct further research taking into account the training environment, psychological factors of athletes, and other physical condition factors associated with the improvement of the 100-meter run of Indonesian National Paralympic Committee (NPC) athletes.